Prevalence of Low Back Pain and Associated Risks in School-Age Children - Santos, Elisiane De Souza [UNESP] (2021)
Background: Low back pain (LBP) is highly prevalent in children and adolescents, while psychosocial, anthropometric, developmental, and lifestyle factors have been associated. However, the evidence is inconsistent from a biological point of view, so identifying predictors of LBP in the 6–12 years children through physical examination should be appropriate. Aims: To estimate the prevalence of LBP and associated factors in schoolchildren in a Brazilian population. Design: Cross-sectional study. Setting: Three schools in Botucatu, Brazil. Participants/Subjects: 377 students from 6-12 years. Methods: Data collection consisted of questions regarding personal history, socioeconomic and anthropometric information, kinesiologic evaluation with anthropometry, lumbar biophotogrammetry, and backpack weight and use. Descriptive analyses were performed, and simple and multiple logistic regression models were used for risk factors. Results: The prevalence of LBP was 27.32% (confidence interval [CI] 95% = 23.07-32.03). The mean age was 8.85 years (± 1.83) in the group with LBP and 8 years (± 1.76) in the group without LBP (p = .006). Variables such as backpack weight (odds ratio [OR] = 1.45, CI 95% = 1.018-2.064) and exceeding 3 hours per day in front of the television (OR = 7.97, CI 95% = 1.957-32.515) increased the chance of LBP in these students. Conclusion: LBP is prevalent in younger schoolchildren, and the factors associated with this outcome can be effectively addressed through the promotion of health measures. LBP in schoolchildren is a musculoskeletal discomfort that negatively affects the quality of life of these individuals and persists in adulthood.